Research on the Optimal Live-Streaming Strategy Under the Influence of Consumer Preferences: Taking Agriculture and Cultural Tourism Enterprise as an Example - Fanyong Meng; Yu Wu (Journal of Theoretical and Applied Electronic Commerce Research)
A series of policy measures have been implemented to support the integration of agriculture and cultural tourism (ACT), positioning it as a pivotal component of the modern rural industrial system. Additionally, the rapid growth of e-commerce live streaming has surpassed the limitations of traditional promotional methods in terms of geographic and media reach. The enterprise can attract more consumer groups through live streaming. This article analyzes the signal game between the ACT enterprise and consumers and discusses how consumer types affect enterprise decision-making in both static and dynamic contexts. We have come to the following conclusion: (1) The severity of punishment for companies that transmit incorrect signals is the main influencing factor for the balance to be established. (2) The more types of consumers an enterprise attracts, the lower its price. (3) The comparison of profits in static and dynamic contexts depends on changes in consumer types and the impact of the first-stage strategy on the second stage.